Kepastian Hukum dalam Pelaksanaan Pengawasan Produk Bersertifikat Halal di Indonesia - Zafitriani, Difanti Ameliananda; Khasanah, Karimatul (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
The implementation of the guarantee of products that have been halal certified is a mandate from the Halal Product Guarantee Law. However, in reality, the technical implementation of periodic supervision of products that have been halal certified has not been specifically regulated in laws and regulations. Therefore, the principle of legal certainty that should be reflected in every regulation is suspected of not being optimally implemented in regulations that guarantee the halalness of halal certified products. This study aims to analyze legal instruments related to halal product guarantees in Indonesia, as well as to examine the legal implications that arise due to legal uncertainty in the technical regulation of supervision of halal certified products. The type of normative legal research with a statutory approach and a conceptual approach. The legal material analysis technique is carried out qualitatively by examining and interpreting laws and regulations, legal doctrines, and the results of theoretical studies to obtain systematic and logical legal arguments related to the regulation of guarantees and supervision of halal products in Indonesia. The results of the study show that halal product guarantee regulations in Indonesia still do not fully reflect the principle of legal certainty, especially regarding post-certification supervision mechanisms. The absence of technical regulations governing the implementation of such supervision has the potential to create legal loopholes and uncertainty in consumer protection and strengthening the halal product guarantee system.